Case-control association study of ABCB1 gene and major depressive disorder in a local Chinese Han population - Zhang, Lin; Xie, Wei-Wei; Wu, Ren-Rong; Yu, Yan; Zhao, Jing-ping; Li, Le-Hua (Neuropsychiatric Disease and Treatment, 2015)
Human P-glycoprotein encoded by the ATP-binding cassette sub-family B member 1 (ABCB1) gene is expressed in the blood-brain barrier. ABCB1 protects the brain from many drugs and toxins such as glucocorticoids through the efflux pump. Recent evidence suggests that a specific allele of the ABCB1 gene confers susceptibility to major depressive disorder (MDD) in the Japanese population. The aim of this study was to explore the association of ABCB1 gene polymorphisms with MDD in a local Chinese Han population. Two hundred and ninety-two MDD patients and 208 unrelated individuals were matched by age and sex and examined using a case-control design. Six single nucleotide polymorphisms (SNPs) of the ABCB1 gene, including rs1045642, rs2032583, rs2032582, rs2235040, rs1128503, and rs2235015, were genotyped by ligase detection reaction and multiplex polymerase chain reaction. Linkage disequilibrium and haplotype analysis were investigated in the two study groups. Significant protection for MDD individuals carrying the TG haplotype of rs1045642-rs2032582 was observed (odds ratio 0.470, 95% confidence interval 0.251-0.897, P=0.01). The rs2032582 (G2677T) and rs1128503 (C1236T) SNPs of ABCB1 showed nominal associations with MDD; the other four SNPs of the ABCB1 gene were not associated with MDD. Chinese individuals carrying the TG haplotype of rs1045642-rs2032582 had a nearly 53% lower risk of developing MDD. To the best of our knowledge, this is the first report to analyze the effect of ABCB1 polymorphism on the risk of MDD in a Chinese population.